PENGEMBANGAN MODEL ASESMEN OTENTIK DALAM PEMBELAJARAN BAHASA - Burhan Nurgiyantoro (Jurnal Cakrawala Pendidikan, 2009)
AbstractDeveloping a Model of Authentic Assessment in Language Learning. Thisstudy aims to produce a guidebook to authentic assessment in language learning,conducted in three years. In the first year, a field survey was conducted to obtaininformation about learning and assessment from Indonesian language teachers ofjunior high schools in Yogyakarta Special Territory and from researcher colleagues.The data were collected through questionnaires, interviews, documents, trainingand assistance, and focus group discussion. The data from the questionnaires wereanalyzed by percentage and other data by the qualitative descriptive technique.The survey shows that (1) generally teachers have not understood andimplemented authentic assessment in language learning, (2) strategies to empowerteachers are implemented through training, workshop, and assistance on designingand implementing authentic assessment, (3) teachers and researcher colleaguesexpect that the guidebook contains concepts of authentic assessment to measurelanguage competence, uses simple language, is easy to follow, and providesconcrete examples, and (4) the guidebook can accommodate the expectations.Keywords: authentic assessment, guidebook, CTL